Spatial interpretation of Arroyo Verde (Gualeguaychú, Entre Ríos Province) in the light of the concepts of territory and place (Huellas, 2020)
This article is part of a progress report for the research project "The territorial productivity of environmental conflicts. The case of the environmental conflict in Gualeguaychú due to the installation and operations of the pulp mill in Fray Bentos (Uruguay).” One of its key objectives is to propose a line of interpretation of the territorial productivity of the environmental conflict, paying particular attention to the contributions of the geography of critical and cultural perspective. From the research work in process, one of the territorial productivities of the conflict is under analysis: the construction, use and meaning of Arroyo Verde, a space produced from the roadblock carried out by the environmental assembly. In this communication, we aim at giving an account of a reflective path that has allowed us to question and interpret the Arroyo Verde space based on the geographical concepts of territory and place.
Keywords: Arroyo Verde; Territory; Place; Gualeguaychú; Environmental Conflict